Halide-based all-solid-state battery interface modification method and halide-based all-solid-state lithium metal battery
By introducing lithium phosphide interface modification layer and lithium phosphorus composite materials into halide-based all-solid lithium metal batteries, the problem of interface deterioration between the halide electrolyte and the lithium negative electrode is solved, and the ion transmission rate and structural stability of the battery are improved. , extends the battery's cycle life.
Patent Information
- Application Number
- CN202411639571.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The interface between the halide electrolyte and the lithium negative electrode deteriorates, resulting in a short circuit in the battery, and the lithium ions diffuse slowly in the metal lithium negative electrode, resulting in lithium dendrites forming and breaking of the electrode material.
Lithium phosphide (Li3P) is introduced as the interface modification layer between the negative electrode side electrolyte and the negative electrode of the halide-based all-solid lithium metal battery, and a lithium-phosphorus composite material is prepared as the negative electrode through a rolling process to improve the ion transmission rate and structural stability sex.
By introducing lithium phosphide interface modification layer and lithium phosphate composite material, the interface stability and ion transfer rate are significantly improved, lithium dendrites are prevented and the electrode material is broken, and the cycle life of the battery is extended.
Smart Images

Figure CN119481371A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of solid-state batteries, and in particular relates to a halide-based all-solid-state battery interface modification method and a halide-based all-solid-state lithium metal battery. Background Art
[0002] Among solid electrolyte materials, halide solid electrolytes are widely used due to their high ionic conductivity (>1mS cm -1 ), high cathode stability, wide operating temperature range, good deformability and other advantages make it one of the most promising solid electrolyte materials. However, the reaction of halide electrolyte with lithium anode leads to battery short circuit, which hinders its further development.
[0003] Although the use of sulfide as the interface modification layer between halide and lithium can effectively slow down the interface deterioration, it cannot fundamentally solve the interface problem of halide electrolyte. Secondly, lithium ions diffuse slowly in the metal lithium negative electrode, and the lithium in the bulk phase cannot participate in the reaction, which makes it easy to form a lithium ion depletion zone at the interface. At the same time, uneven deposition also tends to form lithium dendrites, eventually leading to battery short circuit. Thirdly, due to the huge volume expansion during the lithium ion embedding process, it eventually leads to the fragmentation and collapse of the electrode material. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a halide-based all-solid-state battery interface modification method and a halide-based all-solid-state lithium metal battery. The present invention solves the problem of interface deterioration between the halide electrolyte and the lithium negative electrode by introducing lithium phosphide (Li3P) as an interface modification layer between the negative electrode side electrolyte and the negative electrode of the halide-based all-solid-state lithium metal battery; on this basis, by further optimizing the lithium-phosphorus composite material prepared by the rolling process as the negative electrode of the halide-based all-solid-state lithium metal battery, the ion transfer rate in the negative electrode bulk phase is improved, and the structural stability of the negative electrode is improved.
[0005] The present invention provides a method for modifying the interface of a halide-based all-solid-state battery, comprising the following steps:
[0006] An interface modification layer is arranged between the all-solid electrolyte and the negative electrode on the negative electrode side of the halide-based all-solid-state battery, and the component of the interface modification layer is lithium phosphide.
[0007] The present invention provides a halide-based all-solid-state lithium metal battery, comprising: a positive electrode, a negative electrode and an all-solid-state electrolyte arranged between the positive electrode and the negative electrode, an interface modification layer is arranged between the all-solid-state electrolyte on the negative electrode side and the negative electrode, and a component of the interface modification layer is lithium phosphide.
[0008] Preferably, the active material of the positive electrode is one of nickel-cobalt-manganese ternary positive electrode material, lithium iron phosphate and lithium cobalt oxide.
[0009] Preferably, the positive electrode is a composite positive electrode, and the components of the composite positive electrode include the active material and an all-solid electrolyte on the positive electrode side.
[0010] Preferably, the content of active material in the composite positive electrode is 70-80 wt %.
[0011] Preferably, the negative electrode is a lithium-phosphorus composite negative electrode, and the lithium-phosphorus composite negative electrode comprises a lithium matrix and lithium phosphide embedded in the lithium matrix.
[0012] Preferably, the lithium-phosphorus composite negative electrode is prepared according to the following steps: phosphorus is sprinkled on the surface of a lithium sheet, and the sheet is folded and rolled repeatedly to obtain a lithium-phosphorus composite negative electrode.
[0013] Preferably, the mass ratio of the phosphorus element to the lithium sheet is (1-5):100.
[0014] Preferably, the all-solid electrolyte includes an all-solid electrolyte on the positive electrode side and an all-solid electrolyte on the negative electrode side, the all-solid electrolyte on the positive electrode side is one of Li3InCl6, Li2ZrCl6, Li3YCl6 and Li3YBr6, and the all-solid electrolyte on the negative electrode side is Li6PS5Cl or Li 5.5 PS 4.5 Cl 1.5 .
[0015] Preferably, the mass ratio of the all-solid electrolyte on the positive electrode side, the all-solid electrolyte on the negative electrode side and the interface modification layer is (50-80):(30-50):(10-15).
[0016] Compared with the prior art, the present invention provides a method for modifying the interface of a halide-based all-solid-state battery and a halide-based all-solid-state lithium metal battery. The present invention solves the problem of interface deterioration between the halide electrolyte and the lithium negative electrode by introducing lithium phosphide (Li3P) as an interface modification layer between the negative electrode side electrolyte and the negative electrode of the halide-based all-solid-state lithium metal battery. On this basis, by further preferably using a lithium-phosphorus composite material prepared by a rolling process (the composite material includes a lithium matrix and a fast ion conductor lithium phosphide embedded in the lithium matrix) as the negative electrode of the halide-based all-solid-state lithium metal battery, the ion transfer rate in the negative electrode bulk phase is improved, and the structural stability of the negative electrode is improved. Specifically: (1) lithium phosphide, as a fast ion transfer skeleton, penetrates the interface modification layer and is uniformly embedded in the lithium metal negative electrode, while significantly improving the interface stability, forming a continuous ion transfer path that greatly improves the ion transfer rate on the negative electrode side and in the negative electrode bulk phase; (2) lithium phosphide can effectively inhibit the negative electrode volume expansion effect and significantly improve the structural stability of the lithium negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0018] Figure 1 The LIC / Li symmetrical battery provided in Comparative Example 1 of the present invention is -2 Time-voltage curve under current density;
[0019] Figure 2 The LIC / LPSC / Li symmetrical battery provided in Comparative Example 2 of the present invention is -2 Time-voltage curve under current density;
[0020] Figure 3 The LIC / LPSC / Li3P / Li symmetrical battery provided in Example 1 of the present invention is -2 Time-voltage curve under current density;
[0021] Figure 4 is a CCD curve diagram of the symmetrical battery provided in Example 1 of the present invention;
[0022] Figure 5 is the XRD spectrum of the lithium-phosphorus composite material Li@LiP3 provided in Example 2 of the present invention;
[0023] Figure 6 is a CCD curve diagram of the LIC / LPSC / Li3P / Li@LiP1 symmetric battery provided in Example 3 of the present invention;
[0024] Figure 7 is a CCD curve diagram of the LIC / LPSC / Li3P / Li@LiP3 symmetric battery provided by Example 4 of the present invention;
[0025] Figure 8 is the EIS spectrum of the LIC / LPSC / Li3P / Li@LiP3 symmetric battery provided in Example 4 of the present invention;
[0026] Fig. 9 The LIC / LPSC / Li3P / Li@LiP3 symmetric battery provided by Example 4 of the present invention is -2 Time-voltage curve under current density;
[0027] Fig.10is a CCD curve diagram of the LIC / LPSC / Li3P / Li@LiP5 symmetric battery provided in Example 5 of the present invention;
[0028] Fig.11 This is a graph showing the cycle performance test results of the all-solid-state lithium metal battery NCM811 / LIC / LPSC / Li3P / Li@LiP3 provided in Example 6 of the present invention under 0.5C rate conditions. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The present invention provides a method for modifying the interface of a halide-based all-solid-state battery, comprising the following steps:
[0031] An interface modification layer is arranged between the all-solid electrolyte and the negative electrode on the negative electrode side of the halide-based all-solid-state battery, and the component of the interface modification layer is lithium phosphide.
[0032] The present invention also provides a halide-based all-solid-state lithium metal battery, comprising: a positive electrode, a negative electrode and an all-solid-state electrolyte arranged between the positive electrode and the negative electrode, an interface modification layer is arranged between the all-solid-state electrolyte on the negative electrode side and the negative electrode, and the component of the interface modification layer is lithium phosphide.
[0033] In the all-solid-state lithium metal battery provided by the present invention, the active material of the positive electrode is preferably one of the nickel-cobalt-manganese ternary positive electrode material NCM811, lithium iron phosphate and lithium cobalt oxide; the positive electrode is preferably a composite positive electrode, and the components of the composite positive electrode preferably include the active material and an all-solid-state electrolyte on the positive electrode side, and the all-solid-state electrolyte can specifically be one of Li3InCl6, Li2ZrCl6, Li3YCl6 and Li3YBr6. The content of active material in the composite positive electrode is preferably 70-80wt%, specifically 70wt%, 71wt%, 72wt%, 73wt%, 74wt%, 75wt%, 76wt%, 77wt%, 78wt%, 79wt% or 80wt%.
[0034] In the all-solid-state lithium metal battery provided by the present invention, the negative electrode is preferably a lithium-phosphorus composite negative electrode, and the lithium-phosphorus composite negative electrode includes a lithium matrix and lithium phosphide embedded in the lithium matrix. In the present invention, the lithium-phosphorus composite negative electrode is prepared according to the following steps: phosphorus is sprinkled on the surface of a lithium sheet, and folded and rolled repeatedly to obtain a lithium-phosphorus composite negative electrode; wherein the mass ratio of phosphorus to lithium sheet is preferably (1-5):100, specifically 1:100, 2:100, 3:100, 4:100 or 5:100; the time for repeated folding and rolling is preferably 3-5 minutes.
[0035] In the all-solid-state lithium metal battery provided by the present invention, the all-solid-state electrolyte preferably includes an all-solid-state electrolyte on the positive electrode side and an all-solid-state electrolyte on the negative electrode side; wherein the all-solid-state electrolyte on the positive electrode side is preferably one of Li3InCl6, Li2ZrCl6, Li3YCl6 and Li3YBr6, and the all-solid-state electrolyte on the negative electrode side is preferably Li6PS5Cl or Li 5.5 PS 4.5 Cl 1.5 .
[0036] In the all-solid-state lithium metal battery provided by the present invention, the mass ratio of the all-solid-state electrolyte on the positive electrode side, the all-solid-state electrolyte on the negative electrode side and the interface modification layer is preferably (50-80):(30-50):(10-15), and more preferably 70:40:12.
[0037] The present invention also provides a method for preparing the halide-based all-solid-state lithium metal battery described in the above technical solution, comprising the following steps:
[0038] The all-solid-state electrolyte on the positive electrode side is added into a sealed mold and cold pressed; then the all-solid-state electrolyte on the negative electrode side is added into a sealed mold and cold pressed; then the interface modification layer material is evenly sprinkled on the surface of the all-solid-state electrolyte on the negative electrode side and cold pressed; then the mold is inverted, the positive electrode material is sprinkled on the end of the all-solid-state electrolyte on the positive electrode side and cold pressed; finally, the negative electrode is attached to the interface modification layer side and sealed to obtain a halide-based all-solid-state lithium metal battery.
[0039] The technical solution provided by the present invention solves the problem of interface deterioration between the halide electrolyte and the lithium negative electrode by introducing lithium phosphide (Li3P) as an interface modification layer between the negative electrode side electrolyte and the negative electrode of the halide-based all-solid-state lithium metal battery. On this basis, the present invention further preferably uses a lithium-phosphorus composite material (the composite material includes a lithium matrix and lithium phosphide embedded in the lithium matrix by a rolling process) as the negative electrode of the halide-based all-solid-state lithium metal battery, thereby improving the ion transfer rate in the negative electrode bulk phase and improving the structural stability of the negative electrode. Specifically: (1) lithium phosphide is used as a fast ion transfer skeleton to penetrate the interface modification layer and uniformly embed the lithium metal negative electrode, while significantly improving the interface stability, forming a continuous ion transfer path that greatly improves the ion transfer rate on the negative electrode side and in the negative electrode bulk phase; (2) lithium phosphide can effectively inhibit the negative electrode volume expansion effect and significantly improve the structural stability of the lithium negative electrode. In addition, the lithium-phosphorus composite material in the present invention is preferably prepared by rolling, which is low in cost and suitable for large-scale industrial production.
[0040] For the purpose of greater clarity, the present invention is described in detail with reference to the following examples and comparative examples.
[0041] Comparative Example 1
[0042] The LIC / Li symmetrical battery was prepared. The specific process included: in a glove box filled with argon, commercial lithium sheets with a thickness of 0.45 mm were cut into discs with a diameter of 10 mm; 70 mg of LIC was weighed and evenly sprinkled in a PEEK mold, and pressed at a pressure of 3 tons for 3 to 5 minutes. Subsequently, a lithium sheet with a diameter of 10 mm was attached to the surface of lithium phosphide and sealed to obtain a symmetrical battery LIC / Li.
[0043] The electrical performance of the LIC / Li symmetrical battery prepared in Comparative Example 1 was tested. Figure 1 As shown, Figure 1 The LIC / Li symmetrical battery provided in Comparative Example 1 of the present invention is -2 Time-voltage curve under current density. Figure 1 It can be seen that the LIC / Li symmetric battery short-circuited directly after 2 cycles, and was accompanied by obvious voltage increases in the second and third cycles, which was caused by the reaction between LIC and Li.
[0044] Comparative Example 2
[0045] The LIC / LPSC / Li symmetric battery was prepared. The specific process included: in an argon-filled glove box, commercial lithium sheets with a thickness of 0.45 mm were cut into discs with a diameter of 10 mm; 70 mg of LIC was weighed and evenly sprinkled in a PEEK mold, and compacted at a pressure of 1 ton. Subsequently, 40 mg of LPSC was sprinkled on both sides of the LIC, and pressed at a pressure of 3 tons for 3 to 5 minutes. A 10 mm lithium sheet was attached to the surface of lithium phosphide and then sealed to obtain a symmetric battery LIC / LPSC / Li.
[0046] The electrical performance of the LIC / LPSC / Li symmetrical battery prepared in Comparative Example 2 was tested. Figure 2 As shown, Figure 2 The LIC / LPSC / Li symmetrical battery provided in Comparative Example 2 of the present invention is -2 The time-voltage curve under current density. Figure 2 and Figure 1 By comparison, it can be seen that although the addition of LPSC effectively slows down the reaction between LIC and Li, as the number of cycles increases, the symmetric battery short-circuits after only 150 h of cycling due to the reaction between LPSC and Li, accompanied by a significant voltage increase.
[0047] Example 1
[0048] In an argon-filled glove box, commercial lithium sheets with a thickness of 0.45 mm were cut into discs with a diameter of 10 mm. 70 mg of LIC was weighed and evenly sprinkled on a PEEK mold, compacted at a pressure of 1 ton, 40 mg of LPSC was sprinkled on both sides of the LIC, compacted at a pressure of 2 tons, 12 mg of lithium phosphide was sprinkled on both sides of the LPSC, and pressed at a pressure of 3 tons for 3 to 5 minutes. A 10 mm lithium sheet was attached to the surface of the lithium phosphide and then sealed to obtain a symmetrical battery LIC / LPSC / Li3P / Li. The cycle stability and critical current density (CCD) of the symmetrical battery were tested, and a control group symmetrical battery LIC / LPSC / Li was set up. The results are shown in FIG. Figure 3 and Figure 4 shown.
[0049] Figure 3 The LIC / LPSC / Li3P / Li symmetrical battery provided in Example 1 of the present invention is -2 Time-voltage curve under current density. Figure 3 It can be seen that the LIC / LPSC / Li3P / Li symmetric battery has a -2 It can cycle stably for more than 250 hours at the current density without obvious voltage increase and without short circuit, indicating that using lithium phosphide as the interface modification layer can successfully solve the interface problems of halide-based all-solid-state batteries.
[0050] Figure 4 1 is a CCD curve diagram of a symmetrical battery provided by Example 1 of the present invention, wherein Figure (a) is a symmetrical battery LIC / LPSC / Li, and Figure (b) is a symmetrical battery LIC / LPSC / Li3P / Li. Figure 4 It can be seen that the CCD of the LIC / LPSC / Li3P / Li symmetric battery is increased from 0.8 to 1.0 mA cm -2 , indicating that lithium phosphide as an interface modification layer not only hinders chemical / electrochemical reactions at the interface of solid-state batteries, but also improves the critical current density of symmetrical batteries, enabling lithium metal all-solid-state batteries using lithium phosphide as an interface modification layer to cycle at higher current densities.
[0051] Example 2
[0052] In a glove box filled with argon (Ar) and at room temperature, different masses of phosphorus are evenly sprinkled on the surface of the lithium sheet, and the sheet is repeatedly folded and rolled for 3 to 5 minutes using a low-cost, large-scale commercially produced rolling method; the mass ratios of phosphorus and metallic lithium are 1:100, 2:100, 3:100, 4:100, and 5:100, respectively, and the resulting composite materials are recorded as Li@LiP1, Li@LiP2, Li@LiP3, Li@LiP4, and Li@LiP5, respectively.
[0053] The prepared lithium-phosphorus composite material Li@LiP3 was tested by XRD, and the results are as follows Figure 5 As shown, Figure 5 This is the XRD spectrum of the lithium-phosphorus composite material Li@LiP3 provided in Example 2 of the present invention. Figure 5 It can be seen that the composite negative electrode Li@LiP3 is composed of Li, Li3P and LiOH phases, and no diffraction peak of P is found. This indicates that the phosphorus element can be completely reacted with metallic lithium through the roller pressing process at room temperature to generate a Li3P phase with fast ion transport properties. Therefore, the present invention uniformly constructs a Li3P skeleton with fast ion transport properties inside the metallic Li through the roller pressing process.
[0054] Example 3
[0055] In a glove box filled with argon, a certain mass of lithium sheets was weighed, and phosphorus (weighed at a mass ratio of Li:P of 100:1) was evenly sprinkled on the surface of the lithium sheets. After repeated folding and rolling for 3 to 5 minutes, it was cut into 10 mm discs to obtain the lithium-phosphorus composite negative electrode Li@LiP1; 70 mg of LIC was weighed and evenly sprinkled in a PEEK mold, compacted at a pressure of 1 ton, 40 mg of LPSC was sprinkled on both sides of LIC, compacted at a pressure of 2 tons, 12 mg of lithium phosphide was sprinkled on both sides of LPSC, and pressed at a pressure of 3 tons for 5 minutes. The lithium-phosphorus composite negative electrode Li@LiP1 was attached to the surface of lithium phosphide and then sealed to obtain a symmetrical battery LIC / LPSC / Li3P / Li@LiP1. The CCD of the symmetrical battery was tested, and the results are as follows: Figure 6 shown.
[0056] Figure 6 is a CCD curve diagram of the LIC / LPSC / Li3P / Li@LiP1 symmetric battery provided by Example 3 of the present invention. Figure 6 and Figure 4 By comparison, it can be seen that the CCD of the LIC / LPSC / Li3P / Li@LiP1 symmetric battery is further improved to 1.5 mA cm -2 This enables lithium metal all-solid-state batteries using lithium phosphide as the interface protective layer and lithium-phosphorus composite anode Li@LiP1 to cycle at higher current densities.
[0057] Example 4
[0058] In a glove box filled with argon, a certain mass of lithium sheets was weighed, and phosphorus (weighed at a mass ratio of Li:P of 100:3) was evenly sprinkled on the surface of the lithium sheets. After repeated folding and rolling for 3 to 5 minutes, it was cut into 10 mm discs to obtain the lithium-phosphorus composite negative electrode Li@LiP3; 70 mg of LIC was weighed and evenly sprinkled in a PEEK mold, compacted at a pressure of 1 ton, 40 mg of LPSC was sprinkled on both sides of LIC, compacted at a pressure of 2 tons, 12 mg of lithium phosphide was sprinkled on both sides of LPSC, and pressed at a pressure of 3 tons for 5 minutes. The lithium-phosphorus composite negative electrode Li@LiP3 was attached to the surface of lithium phosphide and then sealed to obtain a symmetrical battery LIC / LPSC / Li3P / Li@LiP3. The electrical properties of the symmetrical battery were tested, and the results are as follows: Figures 7 to 9 shown.
[0059] Figure 7 4 is a CCD curve diagram of the LIC / LPSC / Li3P / Li@LiP3 symmetric battery provided by Example 4 of the present invention. Figure 7 and Figure 6 By comparison, it can be seen that with the increase of phosphorus in the composite negative electrode, the CCD of the LIC / LPSC / Li3P / Li@LiP3 symmetric battery is further improved to 1.8 mA cm-2 This enables lithium metal all-solid-state batteries using lithium phosphide as the interface protective layer and lithium-phosphorus composite anode Li@LiP3 to cycle at higher current densities.
[0060] Figure 8 This is the EIS spectrum of the LIC / LPSC / Li3P / Li@LiP3 symmetric battery provided by Example 4 of the present invention. Figure 8 It can be seen that the symmetrical battery LIC / LPSC / Li3P / Li@LiP3 prepared in this embodiment has an extremely low interface resistance of only 1.96Ωcm 2 .
[0061] Fig. 9 The LIC / LPSC / Li3P / Li@LiP3 symmetric battery provided by Example 4 of the present invention is -2 Time-voltage curve under current density. Fig. 9 It can be seen that the symmetrical battery has a -2 It can stably cycle for more than 1000 hours at the current density, showing extremely excellent cycle stability, indicating the high feasibility of all-solid-state lithium metal batteries constructed with lithium phosphide as the interface modification layer and lithium-phosphorus composite anode.
[0062] Example 5
[0063] In a glove box filled with argon, a certain mass of lithium sheets was weighed, and phosphorus (weighed at a mass ratio of Li:P of 100:5) was evenly sprinkled on the surface of the lithium sheets. After repeated folding and rolling for 3 to 5 minutes, it was cut into 10 mm discs to obtain the lithium-phosphorus composite negative electrode Li@LiP5; 70 mg of LIC was weighed and evenly sprinkled in a PEEK mold, compacted at a pressure of 1 ton, 40 mg of LPSC was sprinkled on both sides of LIC, compacted at a pressure of 2 tons, 12 mg of lithium phosphide was sprinkled on both sides of LPSC, and pressed at a pressure of 3 tons for 5 minutes. The lithium-phosphorus composite negative electrode Li@LiP5 was attached to the surface of lithium phosphide and then sealed to obtain a symmetrical battery LIC / LPSC / Li3P / Li@LiP5. The CCD of the symmetrical battery was tested, and the results are as follows: Fig.10 shown.
[0064] Fig.10 This is a CCD curve diagram of the LIC / LPSC / Li3P / Li@LiP5 symmetric battery provided by Example 5 of the present invention. Fig.10 and Figure 7 By comparison, it can be seen that as the phosphorus content continues to increase, the CCD of the LIC / LPSC / Li3P / Li@LiP5 symmetric battery increases from 1.8 mA cm -2 Reduced to 1.4 mA cm -2, indicating that the optimal lithium:phosphorus mass ratio of the lithium-phosphorus composite anode is 100:3.
[0065] Example 6
[0066] The nickel-cobalt-manganese ternary positive electrode NCM811 and LIC were fully mixed in a mass ratio of 75:25 to obtain a composite positive electrode; 70 mg of LIC was weighed and evenly sprinkled in a PEEK mold, compacted at a pressure of 1 ton, 40 mg of LPSC was sprinkled on one side of LIC, compacted at a pressure of 1.5 tons, 12 mg of lithium phosphide was sprinkled on the LPSC side, compacted at a pressure of 2 tons, about 5 mg of the composite positive electrode was evenly spread on the LIC side, and pressed at a pressure of 3 tons for 5 minutes. Finally, the composite negative electrode Li@LiP3 was cut into 10 mm discs, attached to the surface of lithium phosphide and sealed to obtain an all-solid-state lithium metal battery NCM811 / LIC / LPSC / Li3P / Li@LiP3, and the cycle performance of the symmetrical battery was tested. The results are as follows Fig.11 shown.
[0067] Fig.11 The graph is a graph of the cycle performance test results of the all-solid-state lithium metal battery NCM811 / LIC / LPSC / Li3P / Li@LiP3 provided in Example 6 of the present invention at a rate of 0.5C, wherein (a) is a charge and discharge curve graph of different cycle numbers, and (b) is a curve graph of the change of specific capacity and coulombic efficiency. Fig.11 It can be seen that NCM811 / LIC / LPSC / Li3P / Li@LiP3 has a positive electrode active material loading of 5 mg cm -2 The first cycle discharge capacity under 0.5C rate condition reaches 120.74mAh·g -1 After 100 cycles, the capacity retention rate was 95.72% and there was still no short circuit, showing extremely excellent cycle stability.
[0068] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for interface modification of a halide-based all-solid-state battery, characterized in that: The following steps are involved: An interface modification layer is arranged between the all-solid electrolyte and the negative electrode on the negative electrode side of the halide-based all-solid-state battery, and the component of the interface modification layer is lithium phosphide.
2. A halide-based all-solid-state lithium metal battery, characterized in that: include: A positive electrode, a negative electrode and a fully solid electrolyte arranged between the positive electrode and the negative electrode, an interface modification layer is arranged between the fully solid electrolyte on the negative electrode side and the negative electrode, and the component of the interface modification layer is lithium phosphide.
3. The halide-based all-solid-state lithium metal battery according to claim 2, characterized in that: The active material of the positive electrode is one of nickel-cobalt-manganese ternary positive electrode material, lithium iron phosphate and lithium cobalt oxide.
4. The halide-based all-solid-state lithium metal battery according to claim 3, characterized in that: The positive electrode is a composite positive electrode, and the components of the composite positive electrode include the active material and an all-solid electrolyte on the positive electrode side.
5. The halide-based all-solid-state lithium metal battery according to claim 4, characterized in that: The content of active material in the composite positive electrode is 70-80 wt %.
6. The halide-based all-solid-state lithium metal battery according to claim 2, characterized in that: The negative electrode is a lithium-phosphorus composite negative electrode, and the lithium-phosphorus composite negative electrode comprises a lithium matrix and lithium phosphide embedded in the lithium matrix.
7. The halide-based all-solid-state lithium metal battery according to claim 6, characterized in that: The lithium-phosphorus composite negative electrode is prepared according to the following steps: Sprinkle phosphorus on the surface of the lithium sheet, fold and roll it repeatedly to obtain a lithium-phosphorus composite negative electrode.
8. The halide-based all-solid-state lithium metal battery according to claim 7, characterized in that: The mass ratio of the phosphorus element to the lithium sheet is (1-5):
100.
9. The halide-based all-solid-state lithium metal battery according to claim 2, characterized in that: The all-solid electrolyte comprises an all-solid electrolyte on the positive electrode side and an all-solid electrolyte on the negative electrode side, wherein the all-solid electrolyte on the positive electrode side is one of Li3InCl6, Li2ZrCl6, Li3YCl6 and Li3YBr6, and the all-solid electrolyte on the negative electrode side is Li6PS5Cl or Li 5.5 PS 4.5 Cl 1.5 .
10. The halide-based all-solid-state lithium metal battery according to claim 9, characterized in that: The mass ratio of the all-solid electrolyte on the positive electrode side, the all-solid electrolyte on the negative electrode side and the interface modification layer is (50-80):(30-50):(10-15).
Citation Information
Patent Citations
Composite electrolyte layer structure, electrode assembly and battery
CN116505061A
All-solid-state secondary battery and preparation method thereof
CN117039133A
Ultrathin composite foil and preparation method and application thereof
CN118849595A
A lithium metal negative electrode including a surface protection composite layer and a method for manufacturing the same
KR102568682B1
Lithium battery
WO2008027050A1